Nature versus built - Jais, Noor Maisara; Radin Mohamed, Radin Maya Saphira (Penerbit UTHM, 2020)
Nature is made up of various living and non-living things which is related to plants, animals and other features such as mountains, deserts and seas. They are connected and some of the relationships between members are direct and obvious and ecosystem occurred to balance the amount of living things. Built environment is referring to aspects of creature human-made surroundings. Human activities caused some environmental issues and disturbance the nature. However, the technologies introduce sustainability building and creature as conservation our nature. There also some ways can be practice at house to save the environment.